2005
DOI: 10.1007/s00420-005-0605-y
|View full text |Cite
|
Sign up to set email alerts
|

Functional adrenergic receptor polymorphisms and idiopathic orthostatic intolerance

Abstract: Our current results suggest that the beta1Gly49 polymorphism is protective for IOI. This is likely one of several common genetic loci that may represent modifiers of IOI phenotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Furlan et al found higher LF/HF ratios in OI patients compared with controls in supine phase and during tilt, suggesting a hyperadrenergic state. 40 Also, our observed LF/HF ratios at first survey before training were notably higher in both positions compared with known normal values 26,41 and compared to controls 42 Pϭ0.001). In addition, we noted a reduction of total peripheral resistance after training (Table 5), which suggests a decrease of sympathetic activity.…”
Section: Discussionsupporting
confidence: 46%
“…Furlan et al found higher LF/HF ratios in OI patients compared with controls in supine phase and during tilt, suggesting a hyperadrenergic state. 40 Also, our observed LF/HF ratios at first survey before training were notably higher in both positions compared with known normal values 26,41 and compared to controls 42 Pϭ0.001). In addition, we noted a reduction of total peripheral resistance after training (Table 5), which suggests a decrease of sympathetic activity.…”
Section: Discussionsupporting
confidence: 46%
“…A relationship between OH and mitochondrial DNA mutations was once reported in three families with idiopathic OH [15] . Orthostatic intolerance is also associated with a Gly49 polymorphism of the beta1 receptor gene [35] . Consistent with our results, Tabara et al [19] reported no association between polymorphisms of genes encoding the key components of the traditional RAS pathway and OH in a population-based study.…”
Section: Discussionmentioning
confidence: 99%
“…The following polymorphisms were studied in orthostatic hypotension and chronic orthostatic intolerance: the endothelin‐1 gene (insertion variant in the 5′ UTR), 15 beta‐1 adrenergic receptor gene (polymorphism beta‐1Gly49), 16 the human norepinephrine transporter gene (polymorphism Ala457Pro), 17 Gs protein alpha subunit (polymorphism T131C) 18 and G‐protein beta‐3 subunit (polymorphism C825T), 19 and SCNN1G gene encoding the gamma subunit of the amilorid‐sensitive epithelial sodium channel 19…”
Section: Introductionmentioning
confidence: 99%